Adverse Effects in patients in the treatment of cutaneous Leishmaniasis, Ambo 2010 - Fonseca Livias, Abner (2017)
The study was conducted with the purpose of identifying the adverse effects during the treatment of the Leishmaniasis Skin, that this case we confine ourselves study the effects of sodium Stibogluconato managed to treat leishmaniasis. The population studied was 30 people affected. The method was the correlation and the instrument used was control Sheet the occurrence of adverse events (collaterals). Will study the adverse effects and is contrasted by the correlation of Spearman. The systemic side effects were headache and the general malaise with 3.3% (1) respectively; and the r calculated was 0.119 that indicates a weak correlation. In the adverse effects muscle skeletal, the arthralgias more mialgias are 24% (4) and the r calculated is -0,037 that indicates a negative correlation weak. Regarding the adverse effects gastrointestinal, anorexia amounted to a 40 percent (12) and the r calculated was 0,171 which is close to the average correlation. Referring to the adverse effects dermatological, itching was 83.3 per cent (25) and the r calculated was -0.200 that indicates a negative correlation average. On the other adverse effects, the ulceration was 73.3 per cent (22) and the r calculated was of 0,186 that represents a correlation weak but very close to the average correlation. In conclusion we can indicate that the adverse effects during the treatment of the Skin Leishmaniasis is related to the administration of Stibogluconato sodium in the form weak and average.